1995
DOI: 10.1111/j.1348-0421.1995.tb03252.x
|View full text |Cite
|
Sign up to set email alerts
|

Temperature Effects on Legionella pneumophila Killing by and Multiplication in Phagocytes of Guinea Pigs

Abstract: Abstract:We examined the effects of temperature

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
10
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 32 publications
1
10
0
Order By: Relevance
“…1 as the 10glO increase in the number of CFU per well at intervals. An initial decrease in CFU was observed in NJ and C57BL/6 macrophages at 2 and 4 hr after in vitro phagocytosis, as previously reported on macrophages of guinea pigs (10). In CGD macrophages, however, hardly any initial killing was observed (Fig.…”
supporting
confidence: 66%
See 2 more Smart Citations
“…1 as the 10glO increase in the number of CFU per well at intervals. An initial decrease in CFU was observed in NJ and C57BL/6 macrophages at 2 and 4 hr after in vitro phagocytosis, as previously reported on macrophages of guinea pigs (10). In CGD macrophages, however, hardly any initial killing was observed (Fig.…”
supporting
confidence: 66%
“…Colonies on the agar plates were counted four days after inoculation. ing 2-6 hr after phagocytosis in the same way as macrophages of guinea pigs (10). It was considered that this trait had no relation to the permissive nature of Legionella growth because initial decreases of CFU were equally observed in the macrophages of both NJ (susceptible) and C57BU6 (resistant) mice.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to A. phagocytophilum, several other pathogens such as Legionella pneumophila (Miyamoto et al 1995), the bovine pathogenic bacterium Haemophilus somnus (Czuprynski and Hamilton 1985), the fungal pathogen Histoplasma capsulatum (Medeiros et al 2002), and Burkholderia pseudomallei (Egan and Gordon 1996), the causative agent of melioidosis, were observed to multiply in PMN. Earlier studies demonstrated the intracellular survival of Chlamydia psittaci and Chlamydia trachomatis in PMN (Register et al 1986).…”
Section: Survival Of Pathogens Inside Neutrophilsmentioning
confidence: 98%
“…The febrile rise in body temperature could exert beneficial effects for the host by enhancing immune cell activities (138) and making the internal thermal environment out of the temperature range optimal for pathogen growth (90). Increase in body temperature similar to fever is also observed when animals receive psychological stress.…”
mentioning
confidence: 95%